Strengthening Legal Capacity of Micro, Small, and Medium Enterprises in the Mangrove Ecosystem of Mahakam Delta: Penguatan Kapasitas Hukum Pelaku Usaha Mikro Kecil dan Menengah di Kawasan Ekosistem Mangrove Delta Mahakam - Haris Retno Susmiyati; Grizelda Grizelda; Rahmawati Al Hidayah; Warkhatun Najidah; Wiwik Harjanti; Alfian; Esti Handayani Hardi; Rita Diana; Nurul Puspita Palupi (CONSEN: Indonesian Journal of Community Services and Engagement, 2023)
The economic independence of the community through Micro, Small, and Medium Enterprises (UMKM) is an important priority that supports social economy. Especially during a crisis and pandemic COVID19, UMKM are one of the business actors who are still able to survive when economic activity declines. However, in this great potential, UMKM actors in the mangrove ecosystem in the Mahakam delta area have weaknesses in legal understanding as evidenced by the incomplete licensing requirements, and also do not have an understanding of the urgency and procedures for making contracts and other legal aspects. Therefore, training is needed to increase the legal capacity of UMKM actors. The method used is a training involving UMKM business actors in three stages; UMKM mapping; provide material on opportunities and challenges for UMKM in mangrove ecosystems and legal knowledge for UMKM; preparation of strategic plans for UMKM for mangrove ecosystems. The results of this activity indicate an increase in the legal understanding of UMKM actors and a strategic plan for strengthening UMKM in the mangrove ecosystem in the Delta Mahakam area has been formulated. This encourages the community to participate in protecting and rehabilitating mangrove areas for mutual prosperity. Keywords: Micro, Small and Medium Enterprises ; Mangrove ; Delta Mahakam